Assessing the clinical efficacy of phacoemulsification cataract extraction in treating acute primary angle closure and fellow primary angle closure suspect eyes using AS-OCT - Zhao, Rumin; Geng, Wenhui; Wu, Yunlong; Zhang, Zijian; Zhao, Bojun (Frontiers in Medicine, 2024)
This study aimed to compare anterior segment parameters pre-and postoperatively in acute primary angle closure (APAC) and fellow primary angle closure suspect (PACS) eyes using anterior segment optical coherence tomography (AS-OCT) and evaluate the clinical effectiveness of cataract extraction in the treatment of APAC and fellow PACS eyes.Quantitative measurements of various parameters, including anterior chamber depth (ACD), anterior chamber volume (ACV), lens vault (LV), iridocorneal angle contact index (ITCI), iris thickness (IT), iris volume (IV), and iris curvature (IC), were obtained using Tomey CASIA2 AS-OCT on 60 eyes from 30 patients ( APAC eyes and their fellow PACS eyes) before and after surgery.Simultaneous analysis of the differences between the APAC eyes and fellow PACS eyes in these parameters, visual acuity(VA), and intraocular pressure (IOP) were performed.Results: After surgery, both the APAC eyes and fellow PACS eyes (a total of 60 eyes) showed a significant increase in ACD and ACV,compared to preoperative measurements. Furthermore, LV and ITCI significantly decreased postoperatively. In the PACS group, IC significantly decreased postoperatively, while there was no statistically significant difference in the APAC group. In the APAC group, there was a significant decrease in IOP and improvement in VA at 1 day, 1 week, and the final follow-up compared to preoperative levels. The IOP values in the PACS group were within the normal range across various time points. VA in the PACS group showed significant improvement at 1 week postoperatively and at the final follow-up compared to preoperative levels. Significant differences of VA were observed in the initial, preoperative, first postoperative day, first postoperative week, and final follow-up, with better outcomes observed in the PACS group compared to the APAC group.Lens extraction surgery can significantly improve anterior segment crowding in APAC and PACS eyes. For APAC eyes, combined cataract extraction with intraocular lens implantation and gonioscopy-assisted goniosynechialysis under direct visualization is feasible and safe. Further, in the 2 fellow PACS eye of APAC patients with either significant or mild cataracts, phacoemulsification can maintain or improve preoperative visual acuity to varying degrees and stabilize IOP.